Feasibility study for application of the marine coral powder as a novel adsorbent for Volatile Organic Hydrocarbons - Alireza Mashkoori; Abdul Rahman Bahrami*; Farshid Ghorbani Shahna; Mohammad Javad Zare Sakhvidi; Alireza Koohpaei; Abolfazl Mohammadbeigi (Iranian Journal of Health, Safety and Environment, 2015)
The marine coral has a porous outer surface and it has served in the processes such as water treatment systems, removal of carbon dioxide and adsorption of arsenic. Based on the need for cheap and efficient adsorbents, in sampling, the aim of this study, comparison of the efficiency of marine coral powder and activated charcoal in adsorption of volatile organic hydrocarbons was considered. In this experimental research, a certain concentrations of 8 volatile organic hydrocarbons: (para-Xylene, Chloroform, Carbon tetrachloride, tert-Butanol, Pyridine, Acetone, Ethyl acetate and Diethyl ether) was injected into dynamic atmospheric chamber in the NTP (Normal Temperature and Pressure) conditions. Air sampling was performed with the tube containing marine coral powder as well as the tube of activated charcoal, based on the standard method of NIOSH (National Institute of Occupational Safety and Health) and in the same laboratory conditions. Then samples were injected into the gas Chromatograph apparatus and analytical comparison has been done between the amount of adsorption of hydrocarbons by activated charcoal and coral powder-test and Mann-Whitney were done with SPSS V.20.Findings showed that there was a significant difference between the amount of adsorption of Para-Xylene, carbon tetrachloride, tert-Butanol, Pyridine, acetone and Ethyl acetate hydrocarbons by activated charcoal and coral powder (P<0.05(. The amount of hydrocarbons adsorption by activated charcoal was, more than coral powder significantly (P<0.001). Based on the present research, in sampling of used hydrocarbons, the marine coral powder was less efficient than the activated charcoal, and it is recommended that more works be designed about other techniques such as coating of the marine coral powder in order to the improvement of adsorption capacity for volatile organic hydrocarbons.